ANALISIS QUALITY OF SERVICE JARINGAN WIFI MENGGUNAKAN PROTOKOL MQTT DAN HTTP PADA IMPLEMENTASI PROTOTYPE AQUACULTURE BERBASIS INTERNET OF THINGS UNTUK BUDIDAYA LOBSTER AIR TAWAR - Devi Dama Istianti, Pinky
Technological developments in the field of fisheries in Indonesia are still not aligned with the requirements of the food fisheries industry. However, Indonesia has abundant fishery commodities with high selling values. Cultivators in Indonesia face an obstacle in maintaining an ideal breeding pond environment for the commodities to be cultivated due to differences in climate and other parameters in various regions of Indonesia. There are various commodities with high selling value in both Indonesia and the international market that are difficult to be cultivated such as freshwater lobster. Initially, a prototype was made named Jalasangkuriang but after a few developments and versions, it changed its name to Artemis. Artemis aims to generate heat which will later be channeled into the crayfish spawning pond. This effort is made to assist and facilitate cultivators to obtain appropriate technology to leverage food production in the aquaculture sector. This research consists of three activities, the first one is to create and implement an Artemis prototype, the second is to create a temperature monitoring system, and last but not least is to conduct a network QoS analysis test which is captured using Wireshark. The monitoring system comprises three DS18B20 temperature sensors, one ESP32, one SD card module, and one TFT screen. All data obtained from the monitoring system is sent to the Antares platform using the Telkomsel orbit wi-fi network with two protocols, MQTT and HTTP. The results intended from the implementation of the prototype are to increase the productivity of crayfish breeding. For a super-quality lobster broodstock, it can produce lobster hatchlings 3 times or 300% of the breeding interval. The monitoring system is carried out for 3 months at intervals of changes every 3 hours. The results of using Artemis for environment management have produced consistent temperatures with no fluctuations more than 1°C. On the contrary, if the pond is maintained manually without Artemis, the temperature fluctuation will reach more than 8°C. The next is network QoS analysis testing which is recorded for 1 hour with data sending interval done every 30 seconds. In the MQTT protocol, the throughput value is 18 kbps, the jitter value is 90.96 ms, the delay value is 123,957 ms, and the packet loss value is 0.7%. In the HTTP protocol, the throughput value is 21 kbps, the jitter value is 96.88ms, the delay value is 148.94 ms, and the packet loss value is 0.9%. Based on the stated fact, It can be concluded that the MQTT protocol has better throughput, jitter, delay, and packet loss values than the HTTP protocol, but the difference in values is not significant.